(untitled) (Global Journal of Human-Social Science, 2023)
The pandemic caused by the coronavirus brought the world to a halt placing Brazil in social isolation since March 2020 and bringing repercussions in many areas of society School Education is one of these areas where in-person teaching ceased to occur in practically all countries switching to a forced regime of Remote Education This initiated an emergency transformation in teaching practices Teachers found themselves obligated to reformulate their teaching practices to adapt to technologies that were not necessarily part of their repertoire and the use of the Internet became a major ally for educators at this time The pandemic scenario created a feeling of impermanence and insecurity This moment ends up resembling the concept of liquid and light times mentioned by Bauman 2007 The author states that everything is light molds and dissolves very quickly Thus it is possible to associate this malleability of liquid times with the pandemic context where all changes in teaching are temporary new announcements are made at record speed where new guidelines arise to annul the previous ones and the only certainty is that until there is a definitive solution no decision in educational terms will be permanent